3D bioprinting of proangiogenic constructs with induced immunomodulatory microenvironments through a dual cross-linking procedure using laponite incorporated bioink. (15th January 2022) - Ma, Zhenjiang; He, Hongtao; Deng, Changxu; Ren, Ya; Lu, Dezhi; Li, Wentao; Sun, Xin; Wang, Wenhao; Zhang, Yuxin; Xu, Yuanjing; Zhou, Xiaojun; Zhou, Liang; et al.
Abstract: Vascularization is vital for the survival and functionality of complex tissue-engineered organs, and immune microenvironment is pivotal for effective vascularization. 3D bioprinting is a powerful technique for manufacturing engineered tissues. However, the reconstruction of functionalized vascular scaffolds with immunomodulatory properties through 3D bioprinting has rarely been reported. In this study, we fabricated scaffolds with immunomodulatory properties by incorporating INF-γ loaded laponite into the mixtures of gelatin methacrylate (GelMA)/alginate/4-arm poly(ethylene glycol) acrylate (PEG) (GAP) through coaxial bioprinting method with a sequential cross-linking mechanism that allows for stable production of 3D microfibrous scaffolds. Laponite addition optimized the hydrogel's physical and chemical performance, improved the rheological properties and printing feasibility while enhancing mechanical stress, making the direct fabrication of scaffolds with increased porosity and decreased filament diameter possible. Furthermore, new scaffolds facilitated the expression of chemotactic factors and accelerated EPC migration toward the microfiber peripheries to form a layer of confluent endothelium. Meanwhile, the scaffolds were capable of releasing IFN-γ in the early stage to stimulate macrophage M1 polarization, followed by induction of M2 polarization via the release of Si 4+, Mg 2+ as the degradation of laponite occurred, which successfully improved the sprouting and mature of newly formed vasculature, as well as vascularized bone regeneration. Our results suggested that a combination of GAP-IFN-γ@Lap bioink with a dual-step cross-linking procedure could regulate the local immune microenvironment, aiding the formation of a confluent endothelium, promoting angiogenesis and tissue regeneration, which potentially provides an efficient and simple strategy for developing complex vascularized tissues. Graphical abstract: Image 1